A descriptive inventory of the World War II records and related documents of the Guerilla Movement in Panay Island, 1942-1945, at the Central Philippine University Library - Gabawa, Victory D. (1983)
The research attempted to index volumes 1 to 50 of the 217-volume Panay Guerrilla Documents (PGD), which are mostly textual records of the "Free Panay Forces" which worked cooperatively during the resistance movement against the Japanese occupation on Panay Island and the neighboring islands in 1942 to 1945.